PROFIL PENDERITA DIABETES MELITUS DENGAN HIPOGLIKEMIA DI INSTALASI RAWAT INAP PENYAKIT DALAM RSUD DR. SOETOMO PERIODE 2017 - Putri, Anandia Nafisah; Novida, Hermina; Wardhani, Puspa (Universitas Tribhuwana Tunggadewi, 2021)
Diabetes mellitus can cause hypoglycemia that caused by various factors. This study aimed to determine the profile of general characteristics and metabolic parameters of diabetics with hypoglycemia at the Internal Medicine Inpatient Installation of Dr. Soetomo Hospital on 2017 period. This study was a cross-sectional descriptive study using medical record data of type 1 and type 2 diabetic patients. The total number of hypoglycemic patients in type 2 diabetes was 79 patients. Most patients were in the 50-70 years age group (72.1%), female (60.8%), diabetes duration >5 years (40.5%), and consumsing sulfonylurea (27.8%). Most patients had eGFR value of